An Investigation Into Activated Carbon - Kyriakakis, G (My University, 2015)
The extraction of aurocyanide by activated carbon probably involves the adsorption of neutral ion-pair species [M ^jAuCCN)^. The large hydrophobic aurocyanide anion associates with the cation in order to minimize the disruption of the water structure whereby lowering its free energy
Keywords: Carbon, Activated